1985
DOI: 10.3758/bf03207177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of presentation complexity on rapid-sequential reading

Abstract: In two experiments, text segments were presented successively to a single location on a computercontrolled CRT screen. In Experiment 1, either one or three segments were presented in each display, and in the three-segment displays either one (scrolling) or all segments provided new information. Comprehension was assessed using both multiple-choice questions and passage summarization. Lower comprehension was found in the three-segment displays relative to the onesegment display. In Experiment 2, segments presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The present study illustrates the existence of individual differences for the usefulness of the RSVP procedure: the technique has shown advantages over the conventional page presentation method for a group of less efficient but capable adult readers. This result is striking but is consistent with previous findings that the execution of eye-movement control activities and the increasing complexity of visual display demand attention and processing resources and interfere with comprehension processing (see, e.g., Chen et al, 1985;Gilbert, 1959;Lawrence, 1971;Willows, 1974Willows, , 1978. Inaddition, Breitmeyer (1983) recently reviewed physiological and clinical data in reading and visual exploration and reported that visuosensory and visuomotor deficiencies are both important sources of reading difficulty.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The present study illustrates the existence of individual differences for the usefulness of the RSVP procedure: the technique has shown advantages over the conventional page presentation method for a group of less efficient but capable adult readers. This result is striking but is consistent with previous findings that the execution of eye-movement control activities and the increasing complexity of visual display demand attention and processing resources and interfere with comprehension processing (see, e.g., Chen et al, 1985;Gilbert, 1959;Lawrence, 1971;Willows, 1974Willows, , 1978. Inaddition, Breitmeyer (1983) recently reviewed physiological and clinical data in reading and visual exploration and reported that visuosensory and visuomotor deficiencies are both important sources of reading difficulty.…”
Section: Discussionsupporting
confidence: 82%
“…Because the RSVP technique can eliminate the need for resource-demanding eye-movement control activities in reading (see, e.g., Chen, Healy, & Bourne, 1985, for relevant reviews), and because less efficient readers presumably devote more capacity to activities and processes of reading than do efficient readers, it seems reasonable to predict that this technique would be beneficial to at least less efficient readers, if not to all readers. If this is the RAPID-SEQUENTIAL READING 203 case, the results of the present study should show that RSVP would lead to better performance than would page reading for less efficient readers.…”
mentioning
confidence: 99%
“…Generally, reaction time or accuracy is evaluated as a function of ''set size'' (that is, the number of items in a display). Several previous studies have shown that search field complexity has a significant effect on search duration (Coffey, 1961;Drury & Clement, 1978;Chen, Healy & Bourne, 1985;Muller & Found, 1996;Hogeboom & Leeuwen, 1997); more menu items results in an increase of search time. Complexity of targets and non-targets has been found to affect the detectability of a target (Scharroo, Stalmeier & Boselie, 1994).…”
Section: Study Rationalementioning
confidence: 99%
“…Hypothesis 1: Participants presented with content words in the rapid serial visual presentation group would take more time to complete the task compared to participants presented with full sentences in the traditional text presentation group (e.g., Chen et al, 1985;Proaps & Bliss, 2013;Skelley, Jones, Goodyear, & Roe;2000).…”
Section: Purpose and Hypothesesmentioning
confidence: 99%
“…Research suggests rapidly displaying text segments in a serial fashion can reduce eye movements and increase attention (Potter, 1984). Comprehension of single words and full paragraphs is possible with RSVP, but there are reading comprehension and retention decrements as the rate of presentation increases (e.g., Chen, Healy & Bourne, 1985;Chen & Chien, 2007;Duggan & Payne, 2009;Just & Carpenter, 1980, Potter, 1984. Individuals are often able to comprehend text presented at rates within a range of eight to twelve words per second, similar to rates of traditional text skim reading (e.g., Juola, Ward & McNamara, 1982;Just & Carpenter, 1980;Masson, 1983;Potter, Kroll, & Harris, 1980).…”
Section: Introductionmentioning
confidence: 99%